Environmental performance of China's economic system: integrative perspective of efficiency and productivity - Chen, Yingwen; Yang, Rui; Wong, Christina W. Y.; Miao, Xin (Technological and Economic Development of Economy, 2022)
The high-quality development of regional economic system is inseparable from the collective efforts of multiple economic sectors. Increasing attention has been paid to the environmental performance evaluation of different administrative levels or economic sectors, but integrated research is scarce. Taking the three industries (the primary, secondary and tertiary industries) into account, this paper proposes a data envelopment analysis (DEA) model with parallel network structure to assess the environmental performance of 30 provinces in China from integrative perspective of efficiency and productivity. Then, the Tobit model is adopted to investigate the effects of external factors on the environmental performance. The results show that environmental efficiency of Chinese economy is only 0.4436 during 2010–2019 and the performance of the secondary industry is the highest, followed by the tertiary and the primary industries. Moreover, the environmental efficiency of eastern region is far higher than that of the central or western regions. Technological progress is the main driver of environmental productivity improvement for China’s economic system. Most of the external factors such as energy structure and technology innovation, have different effects on the environmental performance of different regions. Finally, several targeted policy implications are suggested for improving the environmental performance of China’s economic system.